Design rationale for the regulatory approval of medical devices - Sagoo, Jeevan (Cranfield University, 2012)
Design rationale is a methodology aimed at capturing and representing design decisions according to a designated structure. Additionally, these design decisions and their underlying arguments can be made available for examination at a later date. The literature review identified that there is currently a lack of information describing the use of design rationale methods and computational support tools with the medical device domain. Furthermore, the review of literature has also recognised that there are no existing guidelines available for medical device manufacturers and regulatory authorities to follow in order to capture and represent the design decisions in the case of medical devices. Medical devices are instruments which are used for diagnosis, screening, monitoring, or the treating of patients suffering from disease, injury, or disability. Medical devices are products that require rigorous regulation before they can be placed onto the market. If problems are encountered with a device once it has been placed onto the market, the device is recalled by the relevant regulatory authority. Device recalls can often result in the device manufacturers having to evaluate the design decisions that were made during the product development stages in order to address the reported problems and implement a solution. As a result, medical device manufacturers can incur unexpected rework and/or redesign costs, and in even more severe circumstances, incur high litigation costs. This research; reviews the state-of-the-art in design rationale and identifies its key capabilities, analyses design rationale’s feasibility for use with the medical device domain, identifies the regulatory approval processes for medical devices and compares them, analyses the possibilities of utilising design rationale with the regulatory approval of medical devices, and develops a set of guidelines. The guidelines detail the necessary steps that are required to capture and represent the design decisions for medical devices. The utility of this contribution has been verified through the process of validation with experts and researchers.